Intāj al-Lughah fī al-Dimāgh (Dirāsah fī ʿIlm al-Lughah al-ʿAṣabī) - Moh Ismail (Lisanudhad: Jurnal Bahasa, Pembelajaran dan Sastra Arab, 2015)
Thinking is a rational cognitive process that is not directly connected to external objects in the same way as sensory perception; rather, it operates through mental activity. Cognitive activity is closely associated with language, which functions as a medium for thought and communication among members of society. Language itself is realized through a linguistic organization within the brain, the organ that serves as the central regulator of the thinking process. Through the interaction of language and thought, human beings formulate goals that mentally precede the outcomes of their actions. Consequently, thinking is expressed in various forms, including concepts, judgments, reasoning, theories, and other cognitive structures. This article seeks to present several fundamental issues concerning the relationship between language and thought, as well as the cognitive processes that occur within the brain. In its concluding section, the article discusses how linguistic thought is produced in the brain from the perspective of neurolinguistics.